Simple One-Pot Synthesis of New Derivatives of the Macrocyclic Aminal 1,3,7,9,13,15,19,21-octaazapentacyclo-[19.3.1.13,7.19,13.115,19]octacosane (OAPO) (2013)
A series of 2,2′-(dihydropyrimidine-1,3(2H,4H)-diyldimethanediyl)bis(substituted-phenols) was synthesized using a Mannich-type reaction between the macrocyclic aminal 1,3,7,9,13,15,19,21- ctaazapentacyclo[19.3.1.13,7.19,13.115,19]octacosane (OAPO) (1) and substituted phenols in basic media. These previously unreported compounds were separated from the reaction mixture by column chromatography in highly pure form with 25–75% yields. The most stable conformer was predicted using AM1-type semiempirical quantum chemical calculations